2018
DOI: 10.1111/1365-2656.12918
|View full text |Cite
|
Sign up to set email alerts
|

Competitive asymmetry and local adaptation in Trinidadian guppies

Abstract: The outcome of competition between individuals often depends on body size. These competitive asymmetries can drive variation in demographic rates, influencing the ecology and evolution of life histories. The magnitude and direction of such asymmetries differ among taxa, yet little is known empirically about how adaptation to resource limitation alters competitive asymmetries. Here, we investigate the relationship between size‐dependent competitive ability and adaptation to resource limitation. We examined size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…High-and low-density treatments consisted of eight and four fish, respectively, with a 1:1 sex ratio. Hence, densities in our experiment (0.8 and 0.4 fish•L −1 ) were lower than the densities used during the previous generations of selection (6 fish•L −1 ; Renneville et al 2020) and also biologically appropriate for small fish like medaka (e.g., Potter et al 2018). The size structure treatment was applied in both lines to assess the response of each line to size truncation induced by harvesting.…”
Section: Experimental Designmentioning
confidence: 53%
See 2 more Smart Citations
“…High-and low-density treatments consisted of eight and four fish, respectively, with a 1:1 sex ratio. Hence, densities in our experiment (0.8 and 0.4 fish•L −1 ) were lower than the densities used during the previous generations of selection (6 fish•L −1 ; Renneville et al 2020) and also biologically appropriate for small fish like medaka (e.g., Potter et al 2018). The size structure treatment was applied in both lines to assess the response of each line to size truncation induced by harvesting.…”
Section: Experimental Designmentioning
confidence: 53%
“…However, our results also show that the removal of large-sized individuals did not favour increased probability of reproducing for small-sized females, highlighting that direct interference competition alone would probably not influence fitness-related characteristics of smallsized fish. It is worth noting that investigating size-asymmetric competition within each tank as in Potter et al (2018) was not possible here due to the lack of individual size data throughout the experiment. Although we found that the size-structure treatment only played a minor role in structuring fitness components in the populations, we argue that further studies should investigate the complex role of size-dependent asymmetric competition (e.g., following the approach developed by Bassar et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinction between guppy ecotypes is well characterised (Reznick and Endler, 1982;Reznick, 1982;Reznick and Bryga, 1987). However, there is substantial life-history variation among low-predation populations from different streams, including differences in rates of senescence (Reznick et al, 2004(Reznick et al, , 2005, juvenile growth rates (Arendt and Reznick, 2005), basal metabolic rate (Auer et al, 2018), how competitive ability scales with body size (Potter et al, 2019), and in genes associated with living in a low-predation habitat (Whiting et al, 2020). Our results here support the notion that there are multiple mechanistic routes through which the low-predation ecotype can evolve.…”
Section: Biological Variation and Deb Parametersmentioning
confidence: 99%
“…This density dependence is a fundamental principle in ecology and determines the struggle for existence that drives evolution ( 4 ). However, simple metrics, such as population density, entirely ignore differences between individuals in traits such as body size, weight, and condition, although numerous experimental studies and theory clearly indicate that the strength of interaction between individuals should depend on their traits ( 5 8 ).…”
mentioning
confidence: 99%